BUDAYA MUAKHI DAN PEMBANGUNAN DAERAH PERSPEKTIF FILSAFAT SOSIAL PADA KOMUNITAS ADAT PUBIAN DI LAMPUNG - Nurdin, A. Fauzi (Al Qalam, 2009)
Muakhi as a social ethics and moral guidance is actualized in PubianÂLampung society. Muakhi meant confratemily based on human equality is an ethic value in social system that functions to set up the moral consciousness, the sotial, cultural, economic and political adhesive, as well as the nation unitary agglutinant. Muakhi contains the basic values of the social integration that functions to solve the conflicts based on the moral consciousness, the social adhesive and the nation unity. Hence, muakhi may contribute to the moral dimension and social ethics of the regional development. Muakhi as an ethical value in society could be observed, developed and preseroed through various approaches for the development of science and technology.